Evaluation of Effectiveness of an Advertising Campaign: an empirical study - Paiva, Wagner Peixoto de (Review of Business Management, 2007)
This paper describes the process of efficacy evaluation of an advertising campaign (which used two types of media: TV and outdoor media) of a specific product from a multinational company in the health and beauty care segment. It was observed through quantitative analysis that the use of the main medium (TV) showed a moderate to strong correlation with the product’s unit sales throughout the campaign, being responsible for the generation of additional sales. However, the impact of the support media (outdoor) did not generate additional sales alone, but helped to strengthen and to last longer the effects of the main medium. The analysis of the whole campaign showed that it increased sales in the short term but it did This paper describes the process of efficacy evaluation of an advertising campaign (which used two types of media: TV and outdoor media) of a specific product from a multinational company in the health and beauty care segment. It was observed through quantitative analysis that the use of the main medium (TV) showed a moderate to strong correlation with the product’s unit sales throughout the campaign, being responsible for the generation of additional sales. However, the impact of the support media (outdoor) did not generate additional sales alone, but helped to strengthen and to last longer the effects of the main medium. The analysis of the whole campaign showed that it increased sales in the short term but it did not alter the previous level of sales. These non-satisfactory results were also confirmed through marginal analysis of the return on investment. Key-words: Efficacy evaluation. Advertising campaign. Television. Outdoor media.